Women and temporality in literature and cinema : negotiating with timelessness - Ahlawat, Ila, 1989- (Amsterdam University Press, 2021)
Women and Temporality in Literature and Cinema delves into the subject of literary and cinematic women characters entrapped in temporal spaces and their peculiar communication with visibility, enclosure, space and time in the setup of a sexual and temporal discord. It explores subjects such as youth, ageing, remembering, forgetting, and repeating within the larger realm of gendered temporalities that are essentially a nuanced and affective experience.
Keywords: Women in literature.; Time in literature.; Women in motion pictures.; Time in motion pictures.; Femmes dans la littérature.; Temps dans la littérature.; Femmes au cinéma.; Temps au cinéma.; Literature: history and criticism.; Gender studies: women.; LITERARY CRITICISM -- Feminist.; Time in literature; Time in motion pictures; Women in literature; Women in motion pictures; Literature: history & criticism.; Gender studies: women & girls.; Electronic books.